CORRELACIÓN ENTRE EL NIVEL DE TECNIFICACIÓN Y FORMACIÓN SOBRE LAS PRÁCTICAS SANITARIAS, PRÁCTICAS DE ORDEÑO Y MANIPULACIÓN DE LA LECHE Y CALOSTRO EN GRANJA - Moreno Samaniego, Edgar David (2019)
Physiological, technological, health and management factors can affect the productivity and quality of milk in dairy farms. The objective of this work was to analyze in a descriptively and explanatory the practices that can potentially affect the quality of milk and colostrum in 90 dairy farms in two cantons of the province of Chimborazo. Through a questionnaire, information was obtained regarding milking practices, colostrum and feeding colostrum management, milk storage and sanitary management, and descriptive and multivariable analyzes were carried out with the SAS and SPSS programs. It was observed that 1 out of 3 farms analyzed have a significant level of technology, only 3.33% of the owners / managers have higher education and 20% of the farms have received training in good milking practices (C-BPO). Practically these factors, with the exception of the C-BPO, had effects on the management of the farm, with a potential risk for the quality of milk and colostrum. The cluster analysis grouped the farms according to their management, which has allowed us to make a detailed analysis of the groups of farms with potential risks that they have on the quality of milk and colostrum. In this study, for each of these groups, a series of recommendations are offered according to the risk factors, to improve milk quality and colostrum management, in order to be more productive and competitive in the dairy market.